Sustainable by Design: Choice Architecture and the Carbon Footprint of Grocery Shopping. Issue 4 (October 2021) - Panzone, Luca A.; Ulph, Alistair; Hilton, Denis; Gortemaker, Ilse; Tajudeen, Ibrahim Adebisi
The increase in global temperatures requires substantial reductions in the greenhouse emissions from consumer choices. The authors use an experimental incentive-compatible online supermarket to analyze the effect of a carbon-based choice architecture, which presents commodities to customers in high, medium, and low carbon footprint groups, in reducing the carbon footprints of grocery baskets. The authors relate this choice architecture to two other policy interventions: (1) a bonus-malus carbon tax on all grocery products and (2) moral goal priming using an online banner noting the moral importance of reducing one's carbon footprint. Participants shopped from their home in an online store containing 612 existing food products and 39 existing nonfood products for which the authors had carbon footprint data over three successive weeks, with the interventions occurring in the second and third weeks. Choice architecture reduced participants' carbon footprint significantly in the third week by reducing the proportion of choices made in the high-carbon aisle. The carbon tax reduced carbon footprint in both weeks, primarily by reducing overall spend. The goal-priming banner led to a small reduction in carbon footprint in the second week only. Thus, the design of the marketplace plays an important role in achieving the policy objective of reducing greenhouse gas emissions.